(untitled) (Al-Farooq Journal of Sciences, 2026)
This research examines the authority responsible for investigations before the Rome statute with particular focus on the prosecutors powers to initiate investigations proprio motu upon referral by a state council subject to judicial oversight where required. It also highlights the main guarantees afforded to the accused during investigation and trial including the presumption of innocence the right to defence the right to remain silent protection against self- incrimination and the right to fair trial. The study concludes that the Rome statute seeks to balance effective prosecution of international crimes with the protection of the accuseds rights thereby ensuring fairness and due process in international criminal justice.